2018
DOI: 10.1002/jcp.27964
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of exosomes in cardiovascular disorders: From basic science to clinical application

Abstract: Cardiovascular disease (CVD) is the major cause of death globally; therefore, there is a need for the identification of a valid biomarker that accurately predicts the risk of developing CVD, and novel therapeutic approaches for its treatment. Exosomes are very small extracellular vesicles containing protein, lipid, transcription factors, messenger RNAs, noncoding RNA, and nucleic acid contents that are important players in intercellular communication, and that act via long‐range signals or cell‐to‐cell contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 98 publications
0
15
0
1
Order By: Relevance
“…Together these EV populations form an endogenous transport system through which numerous molecules, including various RNA species, are transferred between cells 5 . Over the last decade it has become clear that EV-mediated RNA transfer plays a critical role in the regulation of numerous physiological and pathological processes including immunomodulation, angiogenesis, cell proliferation, neurodegenerative pathologies, cardiovascular events, and tumor metastasis 4,[7][8][9][10][11] . This has resulted in a vast increase in studies on EVs in the context of cell biology, homeostasis, novel targets for therapeutic intervention in pathologies, as well as a potential new source for biomarkers in diagnostics.…”
mentioning
confidence: 99%
“…Together these EV populations form an endogenous transport system through which numerous molecules, including various RNA species, are transferred between cells 5 . Over the last decade it has become clear that EV-mediated RNA transfer plays a critical role in the regulation of numerous physiological and pathological processes including immunomodulation, angiogenesis, cell proliferation, neurodegenerative pathologies, cardiovascular events, and tumor metastasis 4,[7][8][9][10][11] . This has resulted in a vast increase in studies on EVs in the context of cell biology, homeostasis, novel targets for therapeutic intervention in pathologies, as well as a potential new source for biomarkers in diagnostics.…”
mentioning
confidence: 99%
“…Exo are released from cardiomyocytes and enter body fluids 24 , including plasma, serum, and urine. The level of some exosomal lncRNAs is associated with the prognosis of cardiovascular diseases and may be useful as noninvasive biomarkers 25 , 26 . The present study showed that exosomal lncRNA-UCA1 in AMI patients is much higher than in normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) are one of the major concerns in human health, especially coronary artery disease (CAD), which remains the leading cause of global mortality. 95 Currently, circulating biomarkers of CVDs, such as total cholesterol levels and low-density lipoproteins (LDL), and myocardial infarction (MI) prognostic biomarkers, including high-sensitivity C-reactive protein, high-sensitivity cardiac troponin and creatine kinase MB, can only roughly evaluate the risk of the occurrence and progression of the disease but cannot precisely predict whether the process starts or develops. 96,97 In this sense, novel blood-based exosome biopsy can offer a promising platform to assist clinical diagnosis and prediction more accurately.…”
Section: Exosomes In Cardiovascular Diseasesmentioning
confidence: 99%
“…[98][99][100] Simultaneously, circulating exosomes have shown great potential for diagnosis and risk assessment in CVDs. 95 Exosomes in coronary artery disease In CAD, exosomal miR-133a was elevated in injured myocardium and dead cardiomyocytes in particular. 101 Furthermore, miR-146a-abounded exosomes from cardiosphere-derived cells were revealed to promote angiogenesis and inhibit apoptosis, which indicates the therapeutic efficacy of exosomes.…”
Section: Exosomes In Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation